Mutations in the Transmembrane Domain and Cytoplasmic Tail of Hendra Virus Fusion Protein Disrupt Virus-Like-Particle Assembly - Cifuentes-Muñoz, Nicolás (J Virol, 2017)
Hendra virus (HeV) is a zoonotic paramyxovirus that causes deadly illness in horses and humans. An intriguing feature of HeV is the utilization of endosomal protease for activation of the viral fusion protein (F). Here we investigated how endosomal F trafficking affects HeV assembly. We found that the HeV matrix (M) and F proteins each induced particle release when they were expressed alone but that their coexpression led to coordinated assembly of virus-like particles (VLPs) that were morphologically and physically distinct from M-only or F-only VLPs. Mutations to the F protein transmembrane domain or cytoplasmic tail that disrupted endocytic trafficking led to failure of F to function with M for VLP assembly. Wild-type F functioned normally for VLP assembly even when its cleavage was prevented with a cathepsin inhibitor, indicating that it is endocytic F trafficking that is important for VLP assembly, not proteolytic F cleavage. Under specific conditions of reduced M expression, we found that M could no longer induce significant VLP release but retained the ability to be incorporated as a passenger into F-driven VLPs, provided that the F protein was competent for endocytic trafficking. The F and M proteins were both found to traffic through Rab11-positive recycling endosomes (REs), suggesting a model in which F and M trafficking pathways converge at REs, enabling these proteins to preassemble before arriving at plasma membrane budding sites. IMPORTANCE Hendra virus and Nipah virus are zoonotic paramyxoviruses that cause lethal infections in humans. Unlike that for most paramyxoviruses, activation of the henipavirus fusion protein occurs in recycling endosomal compartments. In this study, we demonstrate that the unique endocytic trafficking pathway of Hendra virus F protein is required for proper viral assembly and particle release. These results advance our basic understanding of the henipavirus assembly process and provide a novel model for the interplay between glycoprotein trafficking and paramyxovirus assembly.